The development of the interdisciplinary thematic learning model in vocational education - Marsono; Yoto; Mazarina Devi; Mustakim, Siti Salina (Atlantis Press, 2019)
The Industrial Revolution 4.0 took place along with the rapid development of science and technology so that it spurred every line of life to be able to innovate optimally in facing the challenges of global competition and the emergence of new jobs. The purpose of this study is to develop learning models to provide integrated learning between vocational study programs through Model Interdisciplinary Thematic Learning (INTEL). This research carried out collaboratively by creating a special class collaboration model between 3 vocational study programs (Mechanical Engineering, Electronics Engineering, and Culinary) at the Malang State University Faculty of Engineering. The research method was conducted by research and development of interdisciplinary thematic learning models by taking the theme robotic culinary in Industry 4.0. There are 4 stages of development of INTEL Model, namely: 1) identifying technology in the world of work and student characteristics; 2) analysing instructional learning/competencies that students must have; 3) compiling a collaborative lecture strategy including making syllabus, lesson plans, and lecture modules; and 4) compiling evaluation and evaluation tools for learning implementation. The results of this study are expected to provide real experience in the work world; therefore,it will affect the improvement of competency skills of vocational education students.